PENGARUH RASIO KEUANGAN TERHADAP TINGKAT BAGI HASIL SIMPANAN MUDHARABAH BANK SYARIAH (Studi Empiris pada Bank Syariah Yang Terdaftar Di Bank Indonesia Periode Tahun 2009 – Tahun 2011) (Students' Journal of Accounting and Banking, 2013)
This study aims to analyze the extent of the influence of ROA, FDR, BOPO, and CAR to the level of savings sharing mudaraba, particularly Islamic Banking registered at Bank Indonesia.The population in this study is that banks are on the Islamic financial sector that have been registered in the Bank Indonesia in the period of time between the years 2009 to 2011. This study uses a non-random sampling approach is by purposive sampling, with the criteria of the Bank - Islamic Banking which have the complete data period from 2009 to 2011.Based on hypothesis test results indicate that ROA and CAR significantly positive effect on the level of the deposit mudaraba, FDR is not a significant negative effect on the level of the deposit mudaraba, BOPO significant negative effect on the level of savings results mudarabah.Keywords: Rate of Profit Sharing, ROA, FDR, BOPO, and CAR